2020
DOI: 10.1002/acr.23898
|View full text |Cite
|
Sign up to set email alerts
|

Depression Subtypes in Individuals With or at Risk for Symptomatic Knee Osteoarthritis

Abstract: Objective. The present study was undertaken to identify depression subtypes in individuals with or at risk for symptomatic knee osteoarthritis (OA) and to evaluate differences in pain and disability trajectories between groups.Methods. Participants (n = 4,486) were enrolled in the Osteoarthritis Initiative. Latent class analysis was applied to the 20-item Center for Epidemiologic Studies Depression Scale measured at baseline to identify groups with similar patterns of depressive symptoms, and subtypes were ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Third, the two-factor model could be better interpreted as different symptomatic representation and subtypes of MDD than the unidimensional model [ 50 , 51 ]. A number of empirical studies used machine learning, genetic, and biological approaches to yield strong evidence in favor of MDD consisting of somatic and affective/cognitive factors, rather than one “depression” factor [ 51 53 ]. It is interesting that the best fitting model in this study contradicted the results of Elhai et al (2012), Petersen et al (2015) and Mordeno et al (2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the two-factor model could be better interpreted as different symptomatic representation and subtypes of MDD than the unidimensional model [ 50 , 51 ]. A number of empirical studies used machine learning, genetic, and biological approaches to yield strong evidence in favor of MDD consisting of somatic and affective/cognitive factors, rather than one “depression” factor [ 51 53 ]. It is interesting that the best fitting model in this study contradicted the results of Elhai et al (2012), Petersen et al (2015) and Mordeno et al (2018).…”
Section: Discussionmentioning
confidence: 99%
“…These findings provided evidence for the external validity of the distinction between the MDD somatic and non-somatic factors. Third, the two-factor model could be better interpreted as different symptomatic representation and subtypes of MDD than the unidimensional model [50,51]. A number of empirical studies used machine learning, genetic, and biological approaches to yield strong evidence in favor of MDD consisting of somatic and affective/cognitive factors, rather than one "depression" factor [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Among previous studies, a cross-sectional study described the relationship between depressive symptoms and severity of chronic knee pain assessed by the Numerical Rating Scale (NRS) and the Kellgren-Lawrence Scale 15. Moreover, a recent study revealed a relationship between depressive symptom subtypes and risk for symptomatic knee pain 16…”
Section: Introductionmentioning
confidence: 99%
“…An interesting recent study on individuals with or at risk for symptomatic KOA identified the following four subtypes of depression: asymptomatic, catatonic, anhedonic, and melancholic. Anhedonic and melancholic depression subtypes were suggested to be risk factors for increased pain and disability in individuals who developed and experienced symptomatic KOA [34]. Our results suggest that depression scores in working-age women were significantly correlated with preoperative pain and function, and this association was not reported in working-age men.…”
Section: Discussionmentioning
confidence: 50%